2004
DOI: 10.1126/science.1102792
|View full text |Cite
|
Sign up to set email alerts
|

How Do Small Water Clusters Bind an Excess Electron?

Abstract: The arrangement of water molecules around a hydrated electron has eluded explanation for more than 40 years. Here we report sharp vibrational bands for small gas-phase water cluster anions, (H2O)(4-6)- and (D2O)(4-6)-. Analysis of these bands reveals a detailed picture of the diffuse electron-binding site. The electron is closely associated with a single water molecule attached to the supporting network through a double H-bond acceptor motif. The local OH stretching bands of this molecule are dramatically dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
288
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 277 publications
(303 citation statements)
references
References 36 publications
15
288
0
Order By: Relevance
“…(12)(13)(14)(15) Already a water dimer is capable of binding an excess electron, (12) however, its character is very different from the bulk hydrated species. In small systems, these are weakly bound and very diffuse dipole-bound electrons, which reside at the exterior of the water cluster.…”
Section: Introductionmentioning
confidence: 99%
“…(12)(13)(14)(15) Already a water dimer is capable of binding an excess electron, (12) however, its character is very different from the bulk hydrated species. In small systems, these are weakly bound and very diffuse dipole-bound electrons, which reside at the exterior of the water cluster.…”
Section: Introductionmentioning
confidence: 99%
“…This method has proven very useful in recent studies on the microhydration of anions, for example, SO 4 2-and SF 6 -, 24-26 and on water cluster anions. 27,28 Similar to SO 4 2-, NO 3 -is of sufficiently high symmetry to support degenerate vibrational levels. This degeneracy can be lifted upon asymmetric solvation, leading to a splitting of vibrational levels and additional bands in the experimental IR spectra, thereby directly probing the hydration shell environment.…”
Section: Introductionmentioning
confidence: 99%
“…85 It has been shown that electrons can be stabilized by water clusters via dangling hydrogen atoms, i.e., hydrogen atoms that do not participate in the hydrogen bond. [86][87][88] And then this concept was applied to explain the electronic structure at interfaces. )…”
Section: Adsorption Of Methanol On Tio 2 (110)mentioning
confidence: 99%